Julián Ríos in his own words (2009-2010) - Dunsmoor, Helena (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper brings together two short interviews conducted via email with the Galician author Julián Ríos. The first interview section focusses on Solo a dos voces, a book Ríos co-authored with the Mexican poet Octavio Paz. Ríos’ answers include detailed information about the process of creating the book together and its visual design. Various aspects of collaboration as an artistic and intellectual dialogue are taken up in the third and fourth sections of the paper. These include motifs common to all of Ríos’ work, such as linguistic freedom, unbridled creativity, plurivocity, ever-changing literary identities (readers, narrators, characters and writers), as well as metaphors related to water and trees, both in art and in life. The final section includes a second part, or continuation, of the original interview in full. Here the focus is more broadly set on four of Rios’ interrelated novels, in part to celebrate the republication of Larva nearly forty years after the novel’s first appearance. In the final interview section, Ríos discusses his creative process, voices that materialise into characters, writing as dialogue, dialogue as writing, and to conclude, the infinite possibilities that reading generates.
Keywords: interview; co-autorship; collaboration; Solo a dos voces; text; image; Julián Ríos; Octavio Paz; Larva; Poundemonium; La vida sexual de las palabras; Álbum de Babel; dialogue; plurivocity; reading